Implementability Gaps in Papua Special Autonomy Governance : Regulatory Synchronization, Indigenous Peoples’ Rights, and Sustainable Development - Yohanna YR Watofa; Nur Asmarani; Ali Rahman (Vifada Assumption Journal of Law, 2026)
Purpose: This study examines implementability gaps in Papua Special Autonomy governance by focusing on the disconnection between formal legal mandates and their operational execution, particularly in relation to regulatory synchronization, indigenous peoples’ rights, institutional accountability, and sustainable development. Research Design and Methodology: This study employs a normative-empirical socio-legal approach combining doctrinal mapping of Papua Special Autonomy’s legal framework with a synthesis of peer-reviewed empirical studies published mainly between 2021 and 2025. Findings and Discussion: The findings show that governance underperformance in Papua is associated less with the absence of legal norms than with delayed delegated regulations, heterogeneous technical standards, weak coordination outputs, uneven district capacity, and participation procedures that are not consistently traceable to final policy choices. Implications: This study offers a mechanism-based framework for assessing implementability gaps in special autonomy governance and proposes a staged reform pathway, supported by digital coordination, to strengthen accountability, improve traceable participation, and support more sustainable and rights-sensitive governance in Papua.